The Role of the Second Coordination Sphere in the Biological Activity of Arene Ruthenium Metalla-Assemblies - Therrien, Bruno (Frontiers in Chemistry, 2018)
For nearly 15 years, the biological and biomedical applications of arene ruthenium metalla-assemblies are flourishing. Nowadays, the synthetic strategies to generate arene ruthenium assemblies are well established and these compounds are offering tremendous possibilities in terms of structural diversities and chemical properties. However, the second coordination sphere is often poorly considered, if not ignored, when designing such arene ruthenium metalla-assemblies. These weak interactions (hydrogen bonding, hydrophobic, ionic, electrostatic, van der Waals, π-π stacking) that take place in the solid state or in solution are generally key interactions for the foreseen applications. Therefore, in this review, we want to emphasize this important property of arene ruthenium metalla-assemblies by showing examples dealing with second coordination sphere interactions and how this can be better integrated in the design of these versatile supramolecular metal-based entities.